Penyuluhan keliling mengenai pencegahan stunting di Desa Burai, Ogan Ilir, Indonesia - Najmah; Misnaniarti; Hoirunnisa, Najma; Oktaviandi, Shanti; Firdaus, Zaskia Amirarosa; Putri Yarna, Nafisah Shakira; Dea Ariesty, Sarila Diva; Firzatulloh, Muhammad Buana; Rohmatullah, Muhammad Hersyah; Arfi, Alzikra; Fauziah, Aini; Rahma, Nurul; Naomi, Christara Cicelia; Putri, Sherin Andrea (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2024)
Stunting is still a complex problem that cannot be resolved in Indonesia. Based on the results of the 2022 Indonesian Nutrition Status Survey (SSGI), it was found that 21.6% of Indonesian toddlers were stunted. According to the World Health Organization (WHO) stunting is defined as impaired growth and development of children due to chronic malnutrition and recurrent infections which are characterized by a child's height being below two standard deviations from the WHO median standard. Stunting is not only a nutritional problem caused by food intake but is also closely related to economic problems, sanitation, access to health services, and parenting factors. Kampung Pandai Indralaya Season II is an mothers and children mobile counseling services regarding stunting prevention, personal hygiene, dental health and learning English. During the activity, a stunting survey was carried out to measure parents' knowledge, attitudes and behavior regarding stunting prevention by giving questionnaires and distributing leaflets. The results of the survey were analyzed using a data processing application to see the average value of knowledge, attitudes and behavior of families towards stunting prevention with a sample of 70 respondents. The results showed 42 respondents with good knowledge about stunting prevention (60.0%), 43 respondents (61.4%) with positive attitudes and 39 respondents (55.7%) with good behavior regarding stunting prevention. The majority of respondents have understood the important role of the family in supporting the growth and development of children and reducing the prevalence of stunting.